Comparison The effects of morning and evening Aerobic training on the Inflammatory Markers of Cardiovascular Disease Risk in obes men - محسن عصارزاده نوش آبادی; محسن اکبرپور (Shahid Beheshti University, 2012)
Purpose: The inflammatory markers cause changes in body composition and endocrine activity and lead tocardiovascular disease and diabetes. The aim of present study was to determine the comparison the effects of 12weeks of morning and evening aerobic training . Method: this study was of type Quasi - experiments, 40 nonathletes,obese men were randomly allocated to four groups of morning and evening aerobic training and morningand evening control. Morning and evening training groups performed the aerobic training protocol three sessions perweek for 12 weeks with 75 to 85 percent of maximal heart rate and 15 minutes training per session. The trainingtime was increasingly added 1 minute every two session until the training time reached to 30 minutes .while thecontrol groups were denied doing training programs during the research period. Blood samples (5 cc) were takenfrom the participants at the beginning of the period, week 6 and end of week 12 in order to measure C-reactiveprotein (CRP), interlukin-6 (IL-6) and tumor necrosis factor-alpha (TNF- α). Statistical analysis of the data wasperformed using the 4× 3 factorial ANOVA with statistical process was done using SPSS software, version 15, andthe significance level was considered P<0.05Results: The results showed that morning and evening aerobic trainingdecreased CRP and IL-6 in the experimental groups compared with the control ones. Also, the amount of producedinflammatory markers was less in the evening than in the morning (in the evening training group, the amount ofCRP was 17.1%, 10.5% and 18.87% in week 1, week 6 and week12 and the amount of IL-6 was respectively 21.5%,16.74% and 25.32% lower than that of the morning training group). level of TNF-α decreased in the experimentalgroup mor than control group after 6 and 12 weeks of training, Although this change was notsignificant..Conclusion: According to the results of this study, it was determined that different times of the dayinfluence the compatibility of inflammatory markers caused by aerobic training and these markers show morereduction in the evening. Therefore, it is recommended to young obese men to do exercises in the evening ratherthan morning.